Pengembangan Permainan Urang Gaya Berbasis Budaya Lokal Dalam Menstimulasi Kecerdasan Interpersonal Anak - Prameswari, Titania; Lestariningrum, Anik; Utomo, Hanggara Budi (Efektor, 2021)
The Changes gives both positive and negative effects on the individual, which also occurs in children where there are problems in interaction and communication because of the gadgets that are more widely used in learning. The pandemic era, where children play more gadgets makes interpersonal intelligence increasingly difficult to stimulate. The game namely “urang style” (snakes and ladders of culture) is a solution that can be used to stimulate and optimize interpersonal intelligence for children. The purpose of the research conducted by the author is to create a new play that can be used by PAUD educators in stimulating children's interpersonal intelligence. The subjects in this study were children aged 5-6 years. The research method used is Research and Development (R&D). Implementation of the development using the Barg & Gall model which was simplified into 4 stages including: (1) potential and problem analysis, (2) literature study, (3) product design, (4) design validation. Instruments in data collection related to the observation used. The style game has several advantages including: (1) interesting, (2) interactive, (3) economical, (4) educational. The results of the validity test came from the validator, who concluded that the game of “urang style” was suitable for use and obtained a score of 0.05. The implementation of these results will be the basis if the next stage will be carried out